2004
DOI: 10.1111/j.1365-2222.2004.1918.x
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil activation and cysteinyl leukotriene production in infants with respiratory syncytial virus bronchiolitis

Abstract: In the majority of our subjects with RSV+ve bronchiolitis ECP and LTC4 were detectable in upper airway secretions and were significantly associated with each other. In this clinical setting much of the detected LTC4 within upper airway secretions is likely to originate from the eosinophil, an observation that may have implications for clinical management and for delineation of the underlying mechanisms associated with this illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 34 publications
0
49
0
1
Order By: Relevance
“…Cys-LTs are potent bronchoconstrictors, as well as proinflammatory mediators, and their role in the pathogenesis of airway inflammation and obstruction has been recently recognized as a new target for therapeutic intervention (reviewed in Reference 32). They have been shown to increase in the respiratory secretion of children infected with RSV (33,47) and are associated with RSV-induced wheezing (34). In a mouse model of RSV infection, increased levels of cys-LTs correlate with increased airway responsiveness (35), and either inhibition of LT production (35) or treatment with LT receptor antagonist (36) inhibits AHR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cys-LTs are potent bronchoconstrictors, as well as proinflammatory mediators, and their role in the pathogenesis of airway inflammation and obstruction has been recently recognized as a new target for therapeutic intervention (reviewed in Reference 32). They have been shown to increase in the respiratory secretion of children infected with RSV (33,47) and are associated with RSV-induced wheezing (34). In a mouse model of RSV infection, increased levels of cys-LTs correlate with increased airway responsiveness (35), and either inhibition of LT production (35) or treatment with LT receptor antagonist (36) inhibits AHR.…”
Section: Discussionmentioning
confidence: 99%
“…They have been shown to increase in the respiratory secretion of children infected with RSV (33) and are associated with RSV-induced wheezing (34). We and others have shown that inhibition of LT synthesis (35) or treatment with LT receptor antagonist (36) inhibits lung inflammation and AHR in a mouse model of RSV infection.…”
Section: Effect Of Bha On Rsv-induced Lt Productionmentioning
confidence: 99%
“…Clinical data support the possible involvement of eosinophils in virus-induced exacerbations and increased airway hyperresponsiveness in asthmatic patients: experimental infections with RV16 led to increases in eosinophils and ECP levels in the airways and to airway hyperresponsiveness in atopic asthmatics [15][16][17]. In infants with respiratory syncytial virus (RSV) bronchiolitis, ECP and LTC 4 levels in upper airway secretions are significantly associated [29]. In a guinea pig model of asthma, both airway responsiveness and eosinophil accumulation in the airways increased after a respiratory infection with parainfluenza-3 virus [30].…”
Section: Ifn-b and Eosinophil-endothelial Cell Adhesionmentioning
confidence: 98%
“…Leukotriene C 4 within upper airway secretions in infants with RSV bronchiolitis is likely to originate from the eosinophils [16]. It has been suggested that eotaxin-3 is specifically involved in late-phase asthmatic response, facts which may not fully explain the exacerbation of asthma during or after viral airway infection.…”
mentioning
confidence: 93%